Late to the game? : Capital flows to the Western Balkans - Koczan, Zsoka (IMF Working Papers; Working Paper ;, 2017)
The boom and bust in capital flows to the New Member States of the European Union have received a considerable amount of attention; foreign direct investment and bank flows to the region and countries' participation in regional supply chains have been well-documented. Relatively little has, however, been written about capital flows to the Western Balkans economies, which are often perceived to be 'late arrivals' to large capital flows. This paper aims to examine how capital flows to the Western Balkans compare with flows to the New Member States, in terms of levels as well as dynamics. We find that while financial integration took off somewhat later in the Western Balkans than in the New Member States, it has increased rapidly, despite still much lower capital account openness. Capital inflows as a share of GDP are comparable to those observed in the New Member States, (perhaps surprisingly) diverse in terms of source countries and broadly similar in composition, though with equity shares higher than they were in the New Member States at comparable levels of GDP per capita.